2010
DOI: 10.1155/2010/526487
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Health and Safety Issues in Ontario Sawmills and Veneer/Plywood Plants: A Pilot Study

Abstract: A pilot study was conducted within the Ontario sawmill and veneer/plywood manufacturing industry. Information was collected by postal questionnaire and observational walk-through surveys. Industrial hygiene walk-through surveys were conducted at 22 work sites, and measurements for wood dust, noise, and bioaerosol were taken. The aim of the study was to obtain data on the current status regarding health and safety characteristics and an estimate of wood dust, noise, and bioaerosol exposures. The occupational ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
(10 reference statements)
1
10
0
Order By: Relevance
“…The size of particles produced by band saws of different enterprises had the greatest variation. Moreover, there was a great variation in particle size regardless of the concentration of particulates in each workplace, as has been reported by other authors (Verma et al, 2007;Harper et al, 2004;Tatum et al, 2001;Hinds, 1988).…”
Section: Discussionsupporting
confidence: 80%
“…The size of particles produced by band saws of different enterprises had the greatest variation. Moreover, there was a great variation in particle size regardless of the concentration of particulates in each workplace, as has been reported by other authors (Verma et al, 2007;Harper et al, 2004;Tatum et al, 2001;Hinds, 1988).…”
Section: Discussionsupporting
confidence: 80%
“…Most airborne wood dust particles are >10 μm in size ( Whitehead et al , 1981b ; Hinds, 1988 ; Pisaniello et al , 1991 ; Tatum et al , 2001 ; Harper et al , 2004 ; Verma et al , 2007 ) and relatively little mass of wood dust is found in smaller particle sizes. Occupational wood dust exposure levels are determined by gravimetric analysis, such as NIOSH method 0500 ( NIOSH, 1994 ) and mass measurements are dominated by larger particles as a result of the cubic relation between diameter and mass.…”
Section: Introductionmentioning
confidence: 99%
“…From the selected studies (N = 23), 15 were conducted in the Europe, namely 5 in Norway [29,[36][37][38][39], 4 in Poland [8,[40][41][42], 2 in Switzerland [43,44], 2 in Croatia [45,46], 1 in Finland [47], 1 in Italy [48], and 1 in France [30]. Five studies from Canada [49][50][51][52][53], 1 from Korea [54], and 1 from Iran [55] were also analyzed. The majority of studies (15 out of 23-65.2%) analyzed environmental samples from small and medium size sawmills [18,28,[36][37][38][39][40][41][42][43][44][45][46][47][48][49]51,52], 2 studies (8.7%) were performed in industrial sawmills [29,39], 2 studies (8.7%) in plywood hardwood processing companies [53], 1 (4.4%) in a manufacturing industry [51], 1 (4.4%) in carpentries [48], 1 (4.4%) in pellet p...…”
Section: Characteristics and Data Obtained In The Selected Studiesmentioning
confidence: 99%